Efeitos comportamentais e neuroquímicos da suplementação de ácidos graxos ômega-3 em ratos submetidos à lesão estriatal com 6-OHDA - Barros, Alexandre (2013)
Parkinson's disease (PD) is characterized by a progressive degeneration of dopaminergic neurons in the substantia nigra. The neuronal degeneration may result from the convergence of a number of different pathogenic factors, including apoptosis, excitotoxicity, oxidative stress and inflammation. Many studies emphasize the importance of omega-3 (w-3) in vital processes such as maintenance of the properties of cell membranes, participate in signal transduction and biodynamic activity of neuronal membranes. This study aimed to determine the effects of supplementation with w-3 in the brain of rats subjected to an experimental model of PD induced by 6-OHDA. Male Wistar rats (200-250g) received W-3 (1.5 and 3mg/kg, orally) for 28 days. On the 4th day of treatment was performed 6-OHDA injection into the striatum right (SR). The sham group received saline. On the 25th day of treatment was observed rotational behavior induced by apomorphine and by day 28 the animals were sacrificed. The results showed an increase in the number of apomorphine-induced rotations in the control animals (6-OHDA) compared to the sham group. A motor partial recovery was observed in animals treated with w-3, which reduced the number of rotations around 40 and 75% (1,5 and 3,0 g / kg, respectively). The control group showed a decline of about 70% on locomotor activity when compared to the sham group and treatment with n-3, increased the horizontal exploratory activity. The 6-OHDA promoted increase in MDA content in the prefrontal cortex (PFC), hippocampus (HC) and striatum (CE) (6-OHDA: 75%, 44% and 104%, respectively) compared to sham. The w-3 was capable of reducing the lipid peroxidation about 40%. The w-3 caused a reduction in the concentration of nitrite / nitrate in all areas tested. We observed a significant reduction in the concentration of dopamine (DA) on the ipsilateral controls (61%). However, in animals treated with n-3 this reduction was minor. The results of this study suggest that supplementation with n-3 reversed the behavioral and neurochemical changes of 6-OHDA, with effects potentially beneficial in the treatment of PD.